The Effect of Workload and Job Satisfaction on Turnover Intention of Marketing Employees at PT. Bintang Alam Jaya - Nurfitri, Reisya Sovia (Raudhah Publisher, 2025)
This study examines the impact of workload and job satisfaction on turnover intention among marketing employees at PT. Bintang Alam Jaya. Utilizing a mixed-method approach, the research collected data through interviews, questionnaires, and documentation. The findings reveal that excessive workload, such as high sales targets and additional responsibilities, significantly increases turnover intention. Concurrently, low job satisfaction, influenced by inadequate compensation, lack of recognition, and unfulfilled reward expectations, exacerbates the issue. Statistical analysis demonstrates that workload has a positive correlation with turnover intention, while job satisfaction negatively correlates with it. The study underscores the need for targeted interventions, including workload redistribution, improved reward systems, and fostering a supportive work environment. These measures are critical for reducing turnover rates and enhancing employee retention, contributing to the company’s long-term sustainability.